The social capital strengthening and its development alternatives of waste banks in Java - Heru Subaris Kasjono; Bambang Suwerda; Sri Haryanti; Tengku Mohammad Ariff; Prayudhy Yushananta (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The waste bank (WB) is a government program encouraging community participation in managing waste with social engineering principles. Since its establishment in 2008, only 5% of active customers remain. This study evaluates the management of WB sustainably and the most optimal future alternatives. The research is qualitative and quantitative with a sequential exploratory approach. Data from 35 WB in four provinces (East Java, Central Java, West Java, and DI Yogyakarta) involved 680 respondents. The data was analyzed using the Analytic Network Process (ANP) and Multi-Criteria Decision Analysis (MCDA) to select the optimal alternative. This study found that the three main problems in WB management are institutional (community proactiveness, training, outreach, and capacity building), waste bank capital (triple helix, youth education, and communication forums), and marketing (old selling products, price fluctuations, and market access). Strengthening social capital-based institutions is the main topic of improvement and sustainability, especially networks and trust. The role of government, NGOs, and the community is needed to encourage the sustainability of the WB. The main strategy for solving the problem is strengthening social capital-based institutions, especially networking and value (trust, convenience, and relationships). Assistance is needed from the government or NGOs in managing WB by prioritizing institutional strengthening based on social capital. In addition, encourage all parties to develop an independent waste bank model with reinforcements, especially in institutions, capital, and marketing. Abstrak: Bank sampah merupakan program pemerintah untuk mendorong partisipasi masyarakat dalam mengelola sampah dengan prinsip rekayasa sosial. Sejak didirikan pada tahun 2008, saat ini hanya tersisa 5% nasabah yang aktif. Studi ini mengevaluasi pengelolaan bank sampah secara berkelanjutan dan alternatif masa depan yang paling optimal. Penelitian  bersifat kualitatif dan kuantitatif dengan pendekatan eksplorasi sequential. Penelitian bersifat kualitatif dan kuantitatif dengan pendekatan eksplorasi sequential. Data diperoleh dari 35 Bank Sampah di empat provinsi (Jawa Timur, Jawa Tengah, Jawa Barat, dan DI Yogyakarta), dan melibatkan 680 responden. Data yang terkumpul dianalisis menggunakan Analytic Network Process (ANP) dan Multi-Criteria Decision Analysis (MCDA) untuk memilih alternatif yang optimal. Studi ini menemukan bahwa tiga permasalahan utama pengelolaan bank sampah adalah kelembagaan (proaktif masyarakat, pelatihan, sosialisasi, dan peningkatan kapasitas), modal bank sampah (triple helix, forum komunikasi dan edukasi golongan muda), dan pemasaran (produk laku lama, fluktuasi harga dan akses pasar). Penguatan kelembagaan berbasis modal sosial menjadi topik utama perbaikan dan keberlanjutan, terutama jejaring dan kepercayaan. Peran pemerintah, LSM, dan masyarakat sangat diperlukan untuk mendorong keberlangsungan Bank Sampah. Strategi utama untuk menyelesaikan masalah adalah penguatan kelembagaan berbasis modal sosial, terutama aspek jaringan (networking) dan nilai (trust, convenience and relationships). Diperlukan pendampingan dari pemerintah atau LSM dalam pengelolaan bank sampah dengan mengutamakan penguatan kelembagaan yang berbasis modal sosial. Serta mendorong semua pihak untuk mengembangkan model bank sampah mandiri dengan penguatan-penguatan, terutama pada kelembagaan, permodalan dan pemasaran.